Identification of Obstacles in Using E-Wallet in Semarang - Sri - Widiyati; Th Tyas Listyani; Rikawati - Rikawati (Admisi dan Bisnis, 2021)
The payment system has evolved from cash payments to non-cash payments along with the development of the internet and the emergence of e-commerce. Digitalization in the current payment process provides various options and one of them is an electronic wallet or better known as an e-wallet. Although e-wallet has experienced significant development, users still experience problems in using it. This study aims to identify the obstacles to the use of e-wallet. The sampling method is purposive sampling. The sample used is e-wallet users who are 20 years old and over. Collecting data using a questionnaire and data analyzed by factor analysis. The results of the study show that the obstacles faced in the use of e-wallet are dependence on the internet, servers and electricity. ; merchant limitations and funds must be spent; funds cannot grow (not interest); digital crime.